Matrix metalloproteinases as biomarkers and therapeutic targets in colitis-associated cancer - Sampaio Moura, Natalia; Schledwitz, Alyssa; Alizadeh, Madeline; Patil, Seema A.; Raufman, Jean-Pierre (Frontiers in Oncology, 2024)
Colorectal cancer (CRC) remains a major cause of morbidity and mortality. Therapeutic approaches for advanced CRC are limited and rarely provide long-term benefit. Enzymes comprising the 245member matrix metalloproteinase (MMP) family of zinc-and calcium-dependent endopeptidases are key players in extracellular matrix degradation, a requirement for colon tumor expansion, invasion, and metastasis; hence, MMPs are an important research focus. Compared to sporadic CRC, less is known regarding the molecular mechanisms and the role of MMPs in the development and progression of colitis-associated cancer (CAC)  CRC on a background of chronic inflammatory bowel disease (IBD)  primarily ulcerative colitis and Crohn's disease. Hence, the potential of MMPs as biomarkers and therapeutic targets for CAC is uncertain. Our goal was to review data regarding the role of MMPs in the development and progression of CAC. We sought to identify promising prognostic and therapeutic opportunities and novel lines of investigation. A key observation is that since MMPs may be more active in early phases of CAC, using MMPs as biomarkers of advancing neoplasia and as potential therapeutic targets for adjuvant therapy in those with advanced stage primary CAC rather than overt metastases may yield more favorable outcomes.